2004
DOI: 10.1038/nsmb799
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Ca2+-induced activation of human PAD4

Abstract: Peptidylarginine deiminase 4 (PAD4) is a Ca(2+)-dependent enzyme that catalyzes the conversion of protein arginine residues to citrulline. Its gene is a susceptibility locus for rheumatoid arthritis. Here we present the crystal structure of Ca(2+)-free wild-type PAD4, which shows that the polypeptide chain adopts an elongated fold in which the N-terminal domain forms two immunoglobulin-like subdomains, and the C-terminal domain forms an alpha/beta propeller structure. Five Ca(2+)-binding sites, none of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
437
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(469 citation statements)
references
References 49 publications
14
437
1
Order By: Relevance
“…PAD enzymatic activity is regulated by calcium ions 38. Indeed, intracellular Ca 2+ levels were below the level needed for in vitro PAD activity, indicating that further, as‐yet undefined, regulatory mechanisms may be operating in the joints.…”
Section: Discussionmentioning
confidence: 99%
“…PAD enzymatic activity is regulated by calcium ions 38. Indeed, intracellular Ca 2+ levels were below the level needed for in vitro PAD activity, indicating that further, as‐yet undefined, regulatory mechanisms may be operating in the joints.…”
Section: Discussionmentioning
confidence: 99%
“…The five isotypes in mammals display 70-95% amino acid identity. 7 The five Ca 2+ -binding sites (non-EF-hand motif) exist in PAD4 and are conserved in other isoforms, 8,9 hence, all PADs are thought to contain five Ca 2+ -binding sites. 9 PADs are distinct with regard to substrate and tissue specificity.…”
Section: Peptidylarginine Deiminase and Protein Citrullination In Primentioning
confidence: 99%
“…7 In progenitor and neural cells during development, regulated PAD3 expression is responsible for protein citrullination in response to spinal cord injury, and it is therefore suggested that PAD3 contributes to the loss of regenerative ability. 17 Distinctively, PAD4 (human PAD5 is the human homolog of mouse PAD4) primarily acts in the nucleus because it has a classical monopartite nuclear localization signal at the N-terminal domain, 8 resulting in localization in cell nuclei, where the enzyme citrullinates histones. 18,19 In the nucleus, one of the important functions of PAD4 is to citrullinate histones which regulate gene transcription, this includes not only the arginine residues but also monomethylated arginines.…”
Section: Peptidylarginine Deiminase and Protein Citrullination In Primentioning
confidence: 99%
“…Despite the lack of significant amino acid sequence homology, the core domain structure is similar to those of other arginine-modifying or substituted arginine-modifying enzymes, N ,N -dimethylarginine hydrolase (DDAH) (6), arginine:glycine amidinotransferase (7), arginine:inosamine-phosphate amidinotransferase (8), and human peptidylarginine deiminase (PAD4) (9). Based on the structural similarity and conservation of several key residues in the active site of DDAH and ADI, we proposed a model of arginine binding to ADI in which the guanidinium group is positioned in close proximity to the catalytic Cys 406 (5).…”
mentioning
confidence: 99%